Foundations and applications of the orbital theory in chemistry: A philosophical perspective - Vivas-Reyes, Ricardo; Navarro, Daniela; Cortes, Luis Eduardo (Eclética Química, 2024)
The concept of atomic and molecular orbitals has been a fundamental pillar in modern chemistry, shedding light on the structures and reactivity of chemical compounds. This article examines the evolution and significance of orbital theory, its applications in chemistry, and the ongoing debate about the existence of orbitals from both physics and chemistry perspectives. Philosophical aspects related to the ontology of orbitals are explored, emphasizing the complex interplay between mathematical abstractions and tangible reality. The multifaceted nature of orbitals, their role in quantum mechanics, and their implications for understanding the quantum realm are discussed. While the debate surrounding the ontological status of orbitals remains ongoing, it highlights the profound nature of inquiries into the fundamental essence of reality. This exploration underscores the significance of continuous research and discourse in advancing our understanding of these fundamental constituents of the quantum world.